The impact of coloured filters on the performance of polycrystalline photovoltaic panel in an uncontrolled environment - Armstrong O. Njok; Joel I. Iloke; Manoj Kumar Panjwani; Mangi Fareed Hussain (Institute of Advanced Engineering and Science, 2020)
Photovoltaic modules behave extraordinarily by transforming part of the visible spectrum into electrical energy, and their efficiencies are affected by the nature of radiation (light) reaching them. When light strikes a photovoltaic cell, this light may go through the cell without been absorbed if it is too energetic or if the light possesses low energy it will be absorbed by the cell and cause the electrons to twist and vibrate in their bonds without dislodging them, hence causing the cell to heat up which ultimately leads to a decrease in its overall efficiency. This study is aimed to investigate how photovoltaics respond to different wavelengths of light. For the study to achieve its aim, colour filters were used to ensure that only a particular wavelength of light reaches the photovoltaic module at a time. In the process of collecting data from the solar panel, the solar panel was placed horizontally flat on a platform one meter above sea level facing the sun. Data was first obtained from the solar panel without the filters and after that with the filters placed one at a time and data collected accordingly. The amount of solar power and solar flux anytime a different colour filter was placed on the solar panel were measured. Among the coloured filter used yellow produced the highest efficiency, while blue produced the least efficiency. However, the solar panel was still more efficient when exposed to the natural spectrum.